Ingestion of Flupyradifurone, Pyraclostrobin and Fluxapyroxad Change Melipona scutellaris Behavior and Promote Individuals’ Early Mortality - Inoue, Lais Vieira Bello; Domingues, Caio Eduardo da Costa; Ferreira, Francisco Inácio Paiva; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar (Agricultura Scientia, 2025)
Pesticides are widely used in Brazilian agriculture to protect crops from target organisms. Nevertheless, pesticide use has also been shown to harm beneficial insects, such as bees. Considering the knowledge gap regarding the effects of pesticides on non-Apis species and the importance of stingless bees for ecosystems and human food production, the research aimed to evaluate the survival and behavior of Melipona scutellaris after ingestion of the active ingredients flupyradifurone, pyraclostrobin, and fluxapyroxad, individually and in combination. Therefore, foragers were collected and assigned to experimental groups according to three diets: flupyradifurone 6 ng/μL (IS), pyraclostrobin 0.1 ng/μL and fluxapyroxad 0.05 ng/μL (FN); flupyradifurone 3 ng/μL, pyraclostrobin 0.05 ng/μL, and fluxapyroxad 0.025 ng/μL (IF). The results showed that active ingredients caused early mortality in M. scutellaris foragers. Moreover, just four hours of exposure to IS was sufficient to induce symptoms similar to those caused by neonicotinoids (stumbles, uncoordinated movements, and uncontrolled proboscis extension), whereas exposure to the FN combination induced lethargy in the individuals. The data highlight that even short-term exposure to these active ingredients can cause severe damage to foragers’ physiology, compromising their ability to gather resources for the colony and affecting its overall health.